Curved Laryngopharyngoscope With Flexible Next-Generation Robotic Surgical System for Transoral Hypopharyngeal Surgery: A Preclinical Evaluation. (November 2019) - Eguchi, Kohtaro; Chan, Jason Y. K.; Tateya, Ichiro; Shimizu, Akira; Holsinger, F. Christopher; Sugimoto, Taro
Objectives: The indication of transoral robotic surgery for hypopharyngeal cancer is limited because of poor accessibility. The aim of this study was to explore the efficacy of a curved laryngopharyngoscope used in combination with a next-generation flexible robotic surgical system for accessing and resecting the hypopharynx. Methods: A comparative evaluation of the curved laryngopharyngoscope versus standard straight-blade retractors using the flexible robotic surgical system was conducted on 2 cadavers. End points measured included visualization, accessibility, and ease of dissection for accessing and resecting the hypopharynx. Results: Visualization, accessibility, and dissection were superior with the curved laryngopharyngoscope in all subareas of the hypopharynx. The advantages of accessibility and visualization were much more evident in the cadaver with a high body mass index. Conclusions: These preclinical data suggest that using a curved laryngopharyngoscope in combination with a flexible robotic surgical system may lead to technical innovations concerning transoral surgery of the hypopharynx.